Tell the Truth, B.B. Wolf - Sierra, Judy; Seibold, J.otto (New York : Alfred A. Knopf, 2010)
When Big Bad Wolf, who now lives at the Villain Villa Retirement Residence, is invited to tell his story at the library, he faces the truth about what he did to the three little pigs and decides to make amends.
Accelerated Reader AR